THE PROCESSES ANALYSIS OF URBANIZATION, SPATIAL ARTICULATION, SOCIAL CHANGE AND SOCIAL CAPITAL DIFFERENCE IN THE DYNAMICS OF NEW TOWN DEVELOPMENT IN THE FRINGE AREA OF MAKASSAR CITY, INDONESIA (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2015)
The study aims at analyzing process of urbanization and spatial articulation as the determinant of social change, and finding out social capital differences between migrant and local community in the dynamics of new city development in Metro Tanjung Bunga area. The findings show that spatial articulation in Metro Tanjung Bunga area was initiated by the development of new functions as a stimulating factor of urbanization and infiltrative and expansive migration to Metro Tanjung Bunga area. Spatial articulation causes coexistence of two kinds of mode of production in mastery of reproduction of space which is dominated by capitalist mode of production. It also has an effect of social change and social capital difference between migrant and local community. Occupational differentiation drives process of social interaction between local community and migrant in purpose to establish social relationship and social relations. Economically, the establishment is integrative for basic needs compliance and in effort to maintain existence of local community. Social change portrays differences of social capital, social order and life style between expansive migrant,infiltrative migrant and local community.